2018
DOI: 10.1002/nop2.231
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of new graduate nurses’ health over the first 4 years of practice

Abstract: Aim To examine predictors of Canadian new graduate nurses’ health outcomes over 1 year. Design A time‐lagged mail survey was conducted. Method New graduate nurses across Canada ( N = 406) responded to a mail survey at two time points: November 2012–March 2013 (Time 1) and May–July 2014 (Time 2). Multiple linear regression (mental and overall health) and logistic regression (post‐traumatic stress disorder risk) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 72 publications
(125 reference statements)
0
26
0
2
Order By: Relevance
“…Most consequences were associated with organizational outcomes such as turnover, absenteeism, and work ability. Only two studies reported on consequences related to nurses’ psychological health, one finding a, in this case, higher risk of depression twelve months after baseline [17] and the other finding an increased risk of post-traumatic stress disorder [18] . Thus, we found no studies investigating the psychological health consequences of burnout among nurses for longer than one year.…”
Section: Introductionmentioning
confidence: 99%
“…Most consequences were associated with organizational outcomes such as turnover, absenteeism, and work ability. Only two studies reported on consequences related to nurses’ psychological health, one finding a, in this case, higher risk of depression twelve months after baseline [17] and the other finding an increased risk of post-traumatic stress disorder [18] . Thus, we found no studies investigating the psychological health consequences of burnout among nurses for longer than one year.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have focused on the prevalence and causes of burnout and distress in nurses 6 , 13 – 15 and physicians, 16 18 comparatively fewer studies have addressed these issues among allied health care staff, including pharmacists 19 , 20 and physical, 21 respiratory 22 and occupational 23 , 24 therapists. The aim of this research was to measure the prevalence of burnout and overall distress among allied health care staff practising in a cardiovascular centre of a quaternary hospital network.…”
mentioning
confidence: 99%
“…The transition from student to newly qualified nurse (NQN) is a vulnerable time period 1 2. The challenges of increased clinical responsibility and settling into the clinical work environment can increase stress levels and cause some graduate nurses to consider leaving the profession 3.…”
Section: Contextmentioning
confidence: 99%
“…The latter findings will concern healthcare managers as NQNs are at high risk of making clinical errors in the initial months’ postqualification and collegial support is necessary to improve patient safety 3. Additionally, poor coworker relations are associated with job dissatisfaction which can contribute to nurse burnout 2. Cumulatively, these findings highlight the need for NQN socialisation processes that enhance role transition and improve integration into the complex clinical working environment.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation